Analisis Cerpen “The Enchanted Fish” pada Buku Bahasa Inggris - Studi dan Pengajaran untuk SMA/MA/SMK/MAK dengan Kode Semik (Kajian Semiotik Roland Barthes) - Dewi Cahyaningrum (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2025)
This study examines the short story "The Enchanted Fish," adapted from the fairy tale "The Fisherman and His Wife" by the Brothers Grimm, as additional reading material for high school students. The story contains important moral lessons and uses many connotative signs (words, phrases, and sentences) to convey these messages to its readers, who are English language learners still improving their reading skills. This poses a challenge for students to understand the moral lessons and hidden information in the story. The goal of this study is to reveal the moral values and hidden information in the story using Roland Barthes' semic code theory. The research method used is descriptive qualitative. Data were collected through reading and note-taking. The data analysis follows the interactive model proposed by Miles and Huberman (1994). As a result of the study, it was found that the short story "The Enchanted Fish" uses connotations to convey deep moral messages about greed and avarice and their negative consequences. This analysis also evidences the complexity of the narrative text, which requires reading skills, especially in examining implicit messages and information. The results of this analysis can also serve as a useful reference for teachers in teaching narrative texts and helping students become more critical in reading and understanding stories. Thus, this study contributes to a better understanding of how narrative texts can be used to teach moral and ethical values.